Residential field site training project abstracts - 45th Batch Session: 2002-2003 MBBS Students - Editor, The (Journal of Chittagong Medical College Teachers’ Association, 2009)
doi: 10.3329/jcmcta.v18i1.3820 Journal of Chittagong Medical College Teachers' Association 2007: 18(1):35-41